Maxillofacial Fractures in Elderly Patients: Scoping Review - Roldán C., Victoria (2025)
Maxillofacial fractures, commonly caused by trauma, pose diagnostic and treatment challenges for maxillofacial surgeons. While they are more prevalent in young and active populations, their incidence is increasing in older individuals due to longer life expectancy. Differences in trauma response across generations impact treatment strategies. To analyze available evidence regarding the epidemiology of maxillofacial fractures in geriatric patients. An exploratory literature review was conducted using PRISMA-ScR protocols. PubMed, Scopus, and Web of Science databases were searched with terms such as “Aged,” “Geriatric Dentistry,” “Dental Care for Aged,” combined with “maxillofacial trauma” or “facial trauma.” Inclusion and exclusion criteria were applied for article selection. Based on the PRISMA flowchart, 10 articles were considered in this study. The increasing incidence of maxillofacial fractures in older adults presents clinical challenges and highlights specific risk factors. Evidence suggests reevaluating treatment approaches, recognizing patient vulnerability, and adapting principles to age-related physiological changes. Evidence demonstrates that maxillofacial fractures in the elderly, particularly in the midface region, are often associated with falls and are more prevalent in men based on etiological factors. Comorbidities in old age may exacerbate these fractures, emphasizing specific characteristics in their origin, patterns, and therapeutic approaches.